Consumer Behavior of Modern Society in the Perspective of Islamic Economics: Implications for Individual Financial Balance - Mailatun Linda Sari (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Current advances in digital technology have transformed the shopping habits of modern society. Decisions to purchase goods are now more frequently driven by momentary desires and social prestige pressures (FOMO) rather than actual essential needs. This literature review study aims to analyze such consumptive behavior from the perspective of Islamic economics while also examining its impact on individual financial health. The research summarizes and analyzes various scientific literatures to formulate the root causes of the problem along with possible solutions. The findings reveal that consumptive culture strongly contradicts the teachings of Islamic economics because it disrupts the hierarchy of life priorities (Maqashid Sharia). People tend to force themselves to purchase luxury goods (Tahsiniyyat) even though their basic necessities (Dharuriyyat) may not yet be secure. Such behavior is explicitly categorized as extravagance (israf) and wastefulness (tabdzir). The direct consequence of this lifestyle is the destruction of individual financial balance, triggering expenditures that exceed income and ultimately trapping individuals in digital debt schemes such as pay-later services and online loans. To address this issue, Islamic values offer practical solutions through cultivating a sense of contentment (Qana'ah), discipline in budgeting, adopting a minimalist lifestyle that prioritizes functionality, and increasing social awareness through charity (sadaqah). The implementation of these measures is expected to restore personal economic stability and create a more peaceful life free from the burden of debt.